2021
DOI: 10.3389/fevo.2021.673310
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Effect of Precipitation: Spatial Patterns and Mechanisms of Soil Carbon Emissions

Abstract: The rapid and strong release of CO2 caused by precipitation (known as the pulse effect) is a common phenomenon that significantly affects ecosystem C cycling. However, the degree to which the pulse effect occurs overlarge regional scales remains unclear. In this study, we conducted continuous and high-frequency measurements of soil CO2 release rates (Rs) for 48 h after simulated precipitation, along a precipitation gradient of different grassland types (i.e., meadow, typical, and desert) in Inner Mongolia, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…As the study site is an arid/semi-arid region with a low soil moisture content in its natural state, soil microbes are sensitive to changes in moisture. Lower soil moisture leads to lower microbial activity (Jiang et al, 2021) and higher soil moisture tends to form an anaerobic environment to inhibit microbial activity (Kool et al, 2011). Thus, we hypothesized that, either extremely high or low moisture content is not conducive to microbial decomposition of LOC and SOM; conversely, optimal moisture content conditions (50-70% WHC) would lead to greater CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the study site is an arid/semi-arid region with a low soil moisture content in its natural state, soil microbes are sensitive to changes in moisture. Lower soil moisture leads to lower microbial activity (Jiang et al, 2021) and higher soil moisture tends to form an anaerobic environment to inhibit microbial activity (Kool et al, 2011). Thus, we hypothesized that, either extremely high or low moisture content is not conducive to microbial decomposition of LOC and SOM; conversely, optimal moisture content conditions (50-70% WHC) would lead to greater CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated SOM priming; however, the short-term processes involved in the microbial response to LOC inputs remains unclear. This is due to the rapid response of soil microbes to exogenous substrate inputs, as well as the limitations of measuring technologies (Wang et al, 2016a;Xu et al, 2020;Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For all treatments, we found a general trend of a slight increase in soil pH after the addition of litter, which reached its peak on day 60; after that, an occasional increase was found. When water is added to the soil, the microorganisms get active and break down the soil's organic matter and BL (Jiang et al., 2021; Sharpley et al., 1993) through enzyme activity and alters the soil's acidity (Das et al., 1993; Helyar, 1976). On each sampling date, we observed a general pattern of higher pH in soil with a greater BL application rate and older age (18MH and 30MH) than soil with a lower BL application rate and younger age (18ML and soil with 5 Mg ha −1 of 30‐month‐old BL application [30ML]).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, rainfall can promote microbial activities and strongly stimulate the production of soil CO 2 , leading to an increase in the soil CO 2 concentration, which is called the “stimulation effect”. , Previous studies indicated that organic matter and microorganisms can affect the stimulation effect, increasing the release of CO 2 during rainfall . Especially in arid and semiarid regions, the lower water content has limited impacts on microorganism activities.…”
Section: Discussionmentioning
confidence: 99%
“…46,55 Previous studies indicated that organic matter and microorganisms can affect the stimulation effect, increasing the release of CO 2 during rainfall. 56 Especially in arid and semiarid regions, the lower water content has limited impacts on microorganism activities. When it rains, the soil water content increases sharply, leading to the rapid utilization of available organic matter preserved in arid environments by microorganisms.…”
Section: Effects Of Vegetation Recovery On Soil Co 2 Changesmentioning
confidence: 99%